Augmented Reality in Seismic Risk Management: A Contribution to the Reduction of Non-Structural Damage - Susanna Falsaperla; Danilo Reitano; Gemma Musacchio (Geosciences, 2022)
To increase seismic resilience is one of the challenges the developers of new technologies face to reduce seismic risk. We set up an augmented reality (AR) exhibition with which users’ curiosity was confronted with the opportunity to have a wealth of information on damaging earthquakes that could be a multimedia add-on to the plain “single-layer exhibit”. AR is an emergent technology developed to “augment” reality through various devices; it combines the real world with virtual items, such as images and videos. Our AR exhibition aims to: (i) show the effects of earthquakes even in cases of moderate magnitude; and (ii) promote preventive actions to reduce non-structural damage. It can be customized for different seismic scenarios. In addition, it offers a holistic approach to communicate problems and solutions—with the cost and degree of ease of execution for each solution—to reduce non-structural damage at home, school, and office. Our AR exhibition can do more than just a plain text or a preconceived video: it can trigger fruitful interaction between the presenters, or even the stand-alone poster, and the public. Such interactivity offers an easy engagement to people of all ages and cultural backgrounds. AR is, indeed, extremely flexible in raising recipients’ interest; moreover, it is an appealing tool for the digital native generations. The positive feedback received led us to conclude that this is an effective way to raise awareness and individual preparedness to seismic risk.